Influência do tipo de argamassamento na resistência à compressão de pequenas paredes de alvenaria estrutural cerâmica - Pasquali, Ivair (2007)
The present work has as its main objective to analyze the influence of the mortar bedding in the resistance to compression of small structure masonry walls. For this study were used two types of ceramic blocks (bulk wall blocks and hollow wall blocks), three types of mortar (2 Mpa, 4 Mpa and 10 Mpa) and two types of mortar bedding: whole bedding when the blocks are bedded with mortar in all contact surfaces and longitudinal bedding when the blocks are bedded with only two longitudinal lines (external thickness of the block). Two types dos blocks and mortar were individually characterized through various specific norms tests and afterwards 72 small walls were built. The small walls were built with the pattern dimension of 140 mm x 450 mm x 900 mm being 4 rows in height + u low channel length of one and a half blocks and width of one block. The blocks at the extremities of the walls were already mounted bathed in a cement paste. The analyses of the results show that for the 2 Mpa mortar, bulk wall block and whole bedding the average resistance is 4.68 Mpa and for the 10 Mpa mortar considering the same conditions the average resistance increases to 6.57 Mpa (40.4%). For the 2 Mpa mortar, hollow wall blocks and longitudinal mortar bedding the average resistance is 2.9 Mpa and for the 10 Mpa mortar, considering the same conditions the average resistance increased to 3.33 Mpa (14.8%)